Lactose fermentation by recombinant Saccharomyces cerevisiae strains - Guimarães, Pedro M. R. (2008)
The development of Saccharomyces cerevisiae strains with the ability to ferment lactose has a high biotechnological interest, particularly for cheese whey bioremediation processes with simultaneous bio-ethanol production. We have developed a flocculent S. cerevisiae strain that efficiently ferments lactose to ethanol, using a combination of genetic engineering and evolutionary engineering approaches. This strain fermented efficiently and nearly completely (residual lactose < 3 g·L -1) lactose concentrations up to 150 g·L-1, including 3-fold concentrated cheese whey, producing ethanol titres up to 8% (v/v). The ethanol productivity obtained with this strain (> 1.5 g·L -1·h-1) was higher than that reported for batch or fed-batch fermentations with other lactose-consuming recombinant S. cerevisiae strains. The strain is highly flocculent, a property that makes it interesting for the development of high cell density fermentation processes, which may attain much higher productivity.